Molecular Mechanisms of Malignant Transformation by Low Dose Cadmium in Normal Human Bronchial Epithelial Cells. - Laura Cartularo; Thomas Kluz; Lisa Cohen; Steven S Shen; Max Costa (PLoS ONE)
Cadmium is a carcinogenic metal, the mechanisms of which are not fully understood. In this study, human bronchial epithelial cells were transformed with sub-toxic doses of cadmium (0.01, 0.05, and 0.1 μM) and transformed clones were characterized for gene expression changes using RNA-seq, as well as other molecular measurements. 440 genes were upregulated and 47 genes were downregulated in cadmium clones relative to control clones over 1.25-fold. Upregulated genes were associated mostly with gene ontology terms related to embryonic development, immune response, and cell movement, while downregulated genes were associated with RNA metabolism and regulation of transcription. Several embryonic genes were upregulated, including the transcription regulator SATB2. SATB2 is critical for normal skeletal development and has roles in gene expression regulation and chromatin remodeling. Small hairpin RNA knockdown of SATB2 significantly inhibited growth in soft agar, indicating its potential as a driver of metal-induced carcinogenesis. An increase in oxidative stress and autophagy was observed in cadmium clones. In addition, the DNA repair protein O6-methylguanine-DNA-methyltransferase was depleted by transformation with cadmium. MGMT loss caused significant decrease in cell viability after treatment with the alkylating agent temozolomide, demonstrating diminished capacity to repair such damage. Results reveal various mechanisms of cadmium-induced malignant transformation in BEAS-2B cells including upregulation of SATB2, downregulation of MGMT, and increased oxidative stress.